Accuracy and usability of a geofencing-enabled truancy monitoring system in educational institution - Judhie Putra, Rizky Rachman; Anisyah, Ani; Octaverin, Ghifari (Institute of Computer Science (IOCS), 2024)
Truancy among school-going adolescents remains a persistent issue in education systems globally, impacting academic careers, social relationships, and future prospects. Research indicates that truancy is linked to adverse outcomes, including academic underperformance and significant curricular gaps, which affect both individuals and society. Students who skip school are more susceptible to negative influences that can harm society. To address this issue, we propose a system for monitoring students' locations, enabling parents and teachers to track their whereabouts effectively. This study developed an Android-based student location monitoring application with geofencing to assist parents and teachers during school hours. The geofence is polygon-shaped to accurately represent geographical conditions, utilizing the winding number algorithm to detect a point's position relative to the polygon. However, the algorithm was modified with cross product and dot product calculations to accurately detect points on the polygon's boundary. The waterfall methodology was employed throughout this study. Implemented at PGII 1 Bandung Junior and Senior High School, the application effectively monitored students from a distance. The modification of the winding number algorithm improved accuracy, achieving 100% accuracy in 36 testing scenarios. Evaluation using the System Usability Scale (SUS) yielded an average score of 76.17 from 64 respondents, placing the application in the acceptable category for the acceptability range, grade C on the grade scale, and good for adjective ratings. This indicates that the application is well-accepted and can be effectively used by users